(untitled) (Revista Innova Educación, 2025)
Financial literacy is recognized as an essential competence in higher education due to its direct impact on economic and social well-being. This study aimed to analyze, through a systematic literature review, the role of financial literacy as a university competence, its benefits, key areas, forms of curricular integration, and main implementation challenges. The review followed the PRISMA 2020 guidelines and included articles, books, and book chapters published between 2020 and 2025 in the databases SciELO, RedAlyC, Dialnet, ScienceDirect, Web of Science, and Scopus. After the identification, screening, and eligibility processes, 49 publications were included in the qualitative synthesis. The results reveal a lack of financial education in universities, which is associated with inadequate economic decision-making, higher student indebtedness, and negative effects on the financial and emotional well-being of young people. The literature also highlights clear benefits of its incorporation, such as greater financial autonomy, reduced economic stress, improved decision-making, long-term financial planning, and the promotion of saving, responsible investment, and entrepreneurship. Core areas of financial literacy include budgeting, saving, debt management, credit use, investment, taxation, and insurance, underscoring the need for transversal and interdisciplinary integration within academic programs. However, significant barriers remain, including limited faculty training, institutional constraints, curricular resistance, and low priority in public policy. It is concluded that financial literacy should be formally incorporated into university curricula as a key competence for addressing contemporary economic challenges.